Identifikasi faktor-faktor penyebab rendahnya kemampuan numerasi siswa dalam pembelajaran matematika di Sekolah Dasar - Silfia, Icha; Diana, Ermawati; Lintang, Kironoratri (Papanda Journal of Mathematics and Science Research, 2025)
Numeracy skills are essential competencies that support the development of logical, critical, and systematic thinking in students. However, the reality shows that elementary school students' numeracy skills are still relatively low. This study aims to identify and describe factors that influence the low numeracy skills of fifth-grade students at SD 2 Tumpangkrasak. This study used a qualitative approach with a case study design, involving two key informants. Data collection techniques consisted of observation, interviews, documentation, and numeracy problems analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that students' low numeracy skills were caused by internal and external factors. Internal factors include a lack of learning motivation, anxiety about mathematics, and low self-confidence. Meanwhile, external factors include a non-contextual learning approach, a less supportive classroom environment, and limited parental involvement. In addition, students also experienced difficulties in understanding mathematical symbols, reading and interpreting data in the form of graphs or tables, and using numerical information in decision-making. With this research, teachers and schools are able to identify the factors causing students' low numeracy skills and can overcome students' low numeracy skills